Front-line emergency department nurses' and physicians' assessments of processes of elder-friendly care for quality improvement. (September 2021) - Cetin-Sahin, Deniz; McCusker, Jane; Ciampi, Antonio; Cossette, Sylvie; Vadeboncoeur, Alain; Vu, T. T. Minh; Veillette, Nathalie; Ducharme, Francine; Belzile, Eric; Lachance, Paul-André; Mah, Rick; Berthelot, Simon
Highlights: Nurses and physicians rate geriatric emergency care process indicators similarly in general. Clinicians' ratings can contribute to the global assessment of geriatric care. Continuing educational strategies for geriatric emergency care could be improved. Particular attention is required for family-centered discharge processes. The subscales have concurrent validity against perceived overall quality of geriatric care. Abstract: Introduction: Geriatric emergency department (ED) care has gained increasing importance and interest due to increasing visits in seniors. Aim: Among ED front-line nurses and physicians, to assess and compare ratings of elder-friendly care process indicators, variability in ratings, and concurrent validity of ratings. Methods: Four Quebec EDs' full-time registered nurses and physicians rated their geriatric care using 9 subscales. Nurse and physician subscale scores were compared. Inter-rater variability within disciplines and variability between nurses and physicians were measured. Associations between the subscale scores and perceived overall quality of care were tested. Results: 38 nurses and 36 physicians completed the survey (83% of 89 eligible). Scores differed by discipline for 3 of 9 subscales computed; nurses had higher mean scores on Protocols, Family-Centered Discharge, and Staff Education. Very high variation for Staff Education was found within disciplines. Variations for Family-Centered Discharge differed significantly between nurses and physicians. Almost all subscale scores were significantly positively associated with perceived overall quality of care. Conclusions: ED nurses and physicians rate geriatric care components similarly except for protocols, discharge processes, and continuing education. The subscales have concurrent validity. Results suggest a need for improvement in continuing educational strategies with a particular attention to discharge processes.